2020
DOI: 10.2196/15889
|View full text |Cite
|
Sign up to set email alerts
|

A User-Centered Approach to an Evidence-Based Electronic Health Pain Management Intervention for People With Chronic Pain: Design and Development of EPIO

Abstract: Background Chronic pain conditions are complicated and challenging to live with. Electronic health (eHealth) interventions show promise in helping people cope with chronic illness, including pain. The success of these interventions depends not only on the technology and intervention content but also on the users’ acceptance and adherence. Involving all stakeholders (eg, patients, spouses, health care providers, designers, software developers, and researchers) and exploring their input and preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 68 publications
3
57
0
Order By: Relevance
“…Most patient-oriented apps for people living with chronic pain only provide information about pain or about the illness, including ways to check symptoms and track medication use [ 23 ]. Few eHealth pain-related apps provide information about coping and self-management strategies [ 24 , 25 ], and even though some web-based CBT or ACT-based interventions have been tested in support of people living with chronic pain, findings are still inconclusive and interventions need further testing, also in app format [ 13 , 22 , 26 - 28 ]. Systematic reviews have concluded that eHealth interventions are more likely to be successful if developed with a user-centered focus, increasing the likelihood of matching the user’s needs and requirements [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patient-oriented apps for people living with chronic pain only provide information about pain or about the illness, including ways to check symptoms and track medication use [ 23 ]. Few eHealth pain-related apps provide information about coping and self-management strategies [ 24 , 25 ], and even though some web-based CBT or ACT-based interventions have been tested in support of people living with chronic pain, findings are still inconclusive and interventions need further testing, also in app format [ 13 , 22 , 26 - 28 ]. Systematic reviews have concluded that eHealth interventions are more likely to be successful if developed with a user-centered focus, increasing the likelihood of matching the user’s needs and requirements [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to existing research and recommendations, the current research team has examined users’ (ie, patients living with chronic pain) [ 21 ] and health care providers’ [ 35 ] inputs related to needs and requirements for a potential eHealth pain self-management intervention [ 21 , 35 ]. Incorporating findings [ 21 , 35 ] and combining these with existing clinical and research evidence for the effectiveness of CBT/ACT-type interventions [ 36 - 39 ], the team subsequently designed and developed a cognitive-behavioral pain self-management eHealth intervention called EPIO (inspired by the Greek goddess for the soothing of pain, Epione), aiming to support patients living with chronic pain (ie, chronic pain in general, not pain/pain condition specific) [ 21 , 26 , 35 ]. This study builds on this research line.…”
Section: Introductionmentioning
confidence: 99%
“…The PubMed search led to 35 results, of which 16 articles were included for analysis after the title and abstract assessment (Supplementary Material A). Nine of the identified studies focused on self-management support (40)(41)(42)(43)(44)(45)(46)(47)(48), two were related to health education and information (49,50), and five studies investigated digital health services (51,52) or health promotion and disease prevention interventions (53-55).…”
Section: Innovation Competitiveness Economic Growth and Digital Inmentioning
confidence: 99%
“…The general health status emerged as an essential determinant in the layer of "individual lifestyle factors." Results suggest that patients and health professionals should be enabled to tailor the interventions around individual health needs and preferences, which requires a profound understanding of the needs and routines of the target population and room for personalizing the interventions itself, as well as features such as reminders or motivators (40)(41)(42)(43)(44)(45)(46)(47)55). In some health conditions, empowering, and monitoring features may lead to increased disease distress or be perceived as a control measure.…”
Section: Innovation Competitiveness Economic Growth and Digital Inmentioning
confidence: 99%
See 1 more Smart Citation